Equestrian-related injuries, predictors of fatalities, and the impact on the public health system in Sweden. (March 2019) - Meredith, L.; Thomson, R.; Ekman, R.; Kovaceva, J.; Ekbrand, H.; Bálint, A.
Abstract: Objectives: Horse riding is a popular activity but has also been found to lead to many injuries and even fatalities. No reduction in the numbers of those being admitted to hospital for equestrian-related injuries have been seen in Sweden in recent years. The aim of this work was to examine injuries, fatalities, and predictors of fatalities in equestrian-related activities and to investigate the cost of these injuries to the public health system. Study design: The study is a retrospective analysis of hospital data. Methods: National Swedish hospital and mortality registers were retrospectively examined, inclusive of the years 1997–2014. Logistic regression was used to examine the predictors of fatal injuries, and cost of hospital treatment was considered. Results: Over the study period, there were an observed 29, 850 injured cases and 51 fatalities. Women comprized almost 90% of those injured and 70% of fatalities. The average age was 26.8 years (range 0–91, standard deviation [SD] = 16.1) for injured and 43 years (range 7–78 years, SD = 20.5) for fatal cases. Men dominated both injured and fatal samples in the older age ranges (Fatal: >50 years; Injured: >70 years), although overall numbers were small. Injuries to the head contributed more than any other body region for both injured and fatal cases, and fractures were the most frequently seen injury type. A chi-squared analysis confirmed that injury type and injured body region were not independent of age. Logistic regression examining the association between fatality and age, gender, home region, and year of injury, indicating trends over time, found that there was an increase of 5.1% in the odds of fatality for every year increase in age of the patient and men had 2.2 times higher odds to be in the fatal sample than women. The conservative estimated cost of injury was 1800 Euro per injury event, equating to over 3 million Euro per year. Conclusion: Equestrian-related injury events present a major public health concern. Observed decreases in fatalities suggest improved health care, yet head injury and fatality rates are still high, indicating a need for further intervention. The type of injury changes with the age group, and a better understanding of injury patterns with age is needed to identify protective measures for the different user groups. Highlights: There were on average three fatalities and 1756 injured cases per year. Head injuries contributed 61.4% of fatalities and 29.3% of injuries. The medical cost for injury was 1800 Euro per injury or 3 million Euro annually. There was an increase of 5.1% in the odds of fatality for every year increase in age. Men had 2.2 times higher odds to be in the fatal sample than women.